Lexicology, semantics, and lexicography : selected papers from the fourth G.L. Brook Symposium, Manchester, August 1998 - Coleman, Julie; Kay, Christian (J. Benjamins, 2000)
The papers in this volume show the range and direction of current work in historical semantics and word-studies. There is a strong focus throughout on semantic change and lexical innovation, interpreted within a sociolinguistic, cultural or textual context. Many of the papers draw on the remarkable range of electronic resources now available to historical linguists, notably corpora, dictionaries, bibliographies and thesauruses, and show the effects that these have had in stimulating new lines of research or the re-interpretation of previous conclusions. Cognitive semantics, and especially prot.
Keywords: Lexicology -- Congresses.; Semantics -- Congresses.; Lexicography -- Congresses.; Lexicologie -- Congrès.; Sémantique -- Congrès.; Lexicographie -- Congrès.; Lexicography; Lexicology; Semantics; Historische Lexikografie; Historische Lexikologie; Historische Semantik; Lexicologie.; Lexicografie.; Semantiek.; Manchester <1998>; Englisch.; Conference papers and proceedings